Beyond the 'Capability Trap': Strategies for Strengthening Organizational Capacity in the Implementation of Green Islamic Boarding Schools in Indonesia - Indah Nursanti Widyastuti (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Green infrastructure development in Islamic boarding schools often falls into the capability trap phenomenon, where high-value physical assets fail to function sustainably due to the unpreparedness of social and managerial systems. This policy article aims to formulate a strategy for strengthening organizational capacity to ensure the sustainability of the Green Islamic Boarding School program in Indonesia. The policy methodology used in this study is descriptive qualitative analysis with a policy argumentation approach (William N. Dunn). Problem identification is carried out using the Urgency, Seriousness, and Growth (USG) method to determine priority handling, which is then deepened using a Fishbone diagram to unravel the root causes of the problem in human, method, and organizational aspects. Analysis of policy alternatives is evaluated using the criteria of effectiveness, efficiency, adequacy, justice, responsiveness, and appropriateness (Dunn Scoring). The findings indicate that weak human resource capacity and organizational fragmentation are the most crucial obstacles compared to theological aspects or infrastructure availability alone. Reliance on paternalistic leadership without the support of impersonal SOPs makes it difficult for ecological innovation to be institutionalized. As a transformative solution, this study recommends the establishment of a Ministerial Decree (KMA) concerning a Strategic Plan for Strengthening Human Resource Capacity in Islamic Boarding Schools Based on Sustainability. This policy emphasizes the formalization of environmental management roles through functional positions, the integration of technical literacy into the curriculum, and a shift in key performance indicators (KPIs) from mere physical development to long-term operational effectiveness.